2020
DOI: 10.1111/ffe.13178
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth and delamination mechanisms of Ti/CFRP fibre metal laminates at high temperatures

Abstract: Ti/CFRP (titanium/carbon fibre reinforced polymer) fibre metal laminates (FMLs) are composed of titanium sheets and carbon fibres reinforced PMR (polymerization of monomeric reactants) type polyimide resin. Due to the outstanding heat resistance of the material, it can be used in hypersonic aircraft applications. Fatigue cracks in the metal layer and delamination at metal/fibre interface may occur in long-term high-temperature use processes. However, the behaviour of the fatigue failure at high temperatures ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Carbon fiber-reinforced polymer (CFRP) patches are still of particular interest in various applications in civil engineering [9][10][11][12]. However, there are not many papers devoted to degradation problems in a real operational environment [13][14][15]. Thus, in some cases, the historic stop-hole technique is still attractive based on simple crack "blunting" and re-initiation period [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber-reinforced polymer (CFRP) patches are still of particular interest in various applications in civil engineering [9][10][11][12]. However, there are not many papers devoted to degradation problems in a real operational environment [13][14][15]. Thus, in some cases, the historic stop-hole technique is still attractive based on simple crack "blunting" and re-initiation period [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned advantages make the residual strength models suitable to be used in progressive fatigue damage modeling. [24][25][26] Since cyclic loading occurs in most applications, the majority of the models available in the literature are related to cyclic loading, [27][28][29][30] while the life and damage prediction under sustained load is less addressed. However, the fatigue cycles could be transformed into loading time with the relation t = f  N, where f is loading frequency and N is the number of cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jin et al found that the fatigue crack growth rate in Ti/CFRP nanocomposite was temperature-dependent. The delamination region expanded exponentially with increasing temperature from 20 to 150 °C due to the weakening of the bonding force at the Ti/CFRP interface at high temperatures . For polymer/NPs hybrid nanomaterials, Tsang et al showed that the epoxy polymer embeded with silica NPs was more susceptible to fatigue damage at −40 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The delamination region expanded exponentially with increasing temperature from 20 to 150 °C due to the weakening of the bonding force at the Ti/CFRP interface at high temperatures. 20 For polymer/NPs hybrid nanomaterials, Tsang et al showed that the epoxy polymer embeded with silica NPs was more susceptible to fatigue damage at −40 °C. 21 Clearly, temperature has a great influence on the fatigue endurance of flexible devices, but the underlying physics of how the temperature affects the fatigue endurance is rarely studied, especially for polymer−inorganic NP hybrid devices at low temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%